(untitled) (REMUNOM, 2024)
In 2019, the Anti-Crime Package emerged, the purpose of which was to improve criminal and criminal procedural legislation, modifying article 9-A of the Criminal Execution Law (LEP). Furthermore, article 9-A of the LEP had already been amended and regulated on the compulsory nature of carrying out an exam that collects deoxyribonucleic acid (DNA) with Law No. 12,654/2012, but it was only in 2019 that it reached the contemporary wording. Even with the changes in the LEP, there is still a question about the (un)constitutionality of article 9-A of Law nº 7,210/84. Analyzing the principles of the presumption of innocence and non-self-incrimination, nemo tenetur is detected, the immediate problem arises: The identification of a genetic profile, through the mandatory removal of DNA, is constitutional, as provided for in article 9-A of the Criminal Execution Law according to the principles of presumption of innocence and non-self-incrimination? Thus, the present study has the general objective of investigating the (un)constitutionality of article 9-A of Law No. 7,210/1984, based on the principles of nemo tenetur se detegere, that is, the guarantee of not self-incriminating, referring, to the principles of presumption of innocence and non-self-incrimination, using the aforementioned legal guidelines as justification. The methodology was directed towards a qualitative perspective and bibliographical research carried out in articles and doctrines. In conclusion, there is a huge discussion about the (un)constitutionality of the legal diploma, leaning towards illegality, resulting in legal consequences and constitutional violations.